During and beyond a pandemic: Publishing learning and teaching research through COVID-19 - Crawford, Joseph (Journal of University Teaching and Learning Practice, 2021)
The novel coronavirus pandemic (COVID-19) has been a prevailing topic in contemporary higher education literature over the past year. The initial and emerging responses will be ongoing sources of critical reflection and future research. This commentary seeks to reflect on three types of manuscripts we are reviewing frequently within the Journal of University Teaching and Learning Practice, and those published elsewhere. Despite our best efforts, many publications overemphasize the present context without contextualising previous insights, or retain previous knowledge without application to contemporary practice. This commentary provides a brief review of manuscripts with pre-COVID-19 data, COVID-19-specific data, and future focused reflections. The objective is to posit mechanisms by which these manuscripts can serve as a practical account, be useful to current practitioners, and create ongoing opportunities to imagine a future higher education that serves the broad academic community well.